In‐Hospital Worsening Heart Failure and Associations With Mortality, Readmission, and Healthcare Utilization. Issue 4 (11th July 2014) - DeVore, Adam D.; Hammill, Bradley G.; Sharma, Puza P.; Qualls, Laura G.; Mentz, Robert J.; Waltman Johnson, Katherine; Fonarow, Gregg C.; Curtis, Lesley H.; Hernandez, Adrian F.
Abstract : Background: A subset of patients hospitalized with acute heart failure experiences worsening clinical status and requires escalation of therapy. Worsening heart failure is an end point in many clinical trials, but little is known about its prevalence in clinical practice and its associated outcomes. Methods and Results: We analyzed inpatient data from the Acute Decompensated Heart Failure National Registry linked to Medicare claims to examine the prevalence and outcomes of patients with worsening heart failure, defined as the need for escalation of therapy at least 12 hours after hospital presentation. We compared patients with worsening heart failure to patients with an uncomplicated hospital course and patients with a complicated presentation. Of 63 727 patients hospitalized with acute heart failure, 11% developed worsening heart failure. These patients had the highest observed rates of mortality, all‐cause readmission, and Medicare payments at 30 days and 1 year after hospitalization ( P  < 0.001 for all comparisons). The adjusted hazards of 30‐day mortality were 2.56 (99% CI, 2.34 to 2.80) compared with an uncomplicated course and 1.29 (99% CI, 1.17 to 1.42) compared with a complicated presentation. The adjusted cost ratios for postdischarge Medicare payments at 30 days were 1.35 (99% CI, 1.24 to 1.46) compared with an uncomplicated course and 1.11 (99% CI, 1.02 to 1.22) compared with a complicated presentation. Conclusions: In‐hospital worsening heart failure was common and was associated with higher rates of mortality, all‐cause readmission, and postdischarge Medicare payments. Prevention and treatment of in‐hospital worsening heart failure represents an important goal for patients hospitalized with acute heart failure.